Studi Pertumbuhan Kristal Glisin dalam Matriks Kitosan sebagai Media Praktikum Sensor Piezoelektrik Berbasis Biopolimer bagi Mahasiswa Pendidikan Fisika - Nurhandayani Nurhandayani; Nurvadillah Angraini; Yusnita Sari; Nurul Amalia Aris (Universitas Garut, 2025)
This study aims to examine the growth of glycine crystals in a chitosan matrix and its potential as a biopolymer-based piezoelectric sensor laboratory medium for physics education students. The research methodology involved synthesizing chitosan-glycine films using a solution method, then observing the growth and morphology of glycine crystals visually and using simple optical instruments. The results showed that glycine was able to grow in the chitosan matrix with clearly and evenly formed crystal morphology, which was influenced by the interaction between glycine and the chitosan matrix. The resulting film structure was flexible and transparent, making it suitable for use as an observation medium in practical activities. This study was limited to observing crystal growth without measuring electrical properties or piezoelectric response. Practically, the results of this study provide a simple, inexpensive, and environmentally friendly alternative laboratory medium for introducing the concepts of crystal growth and piezoelectric materials. The social implications support sustainable science learning through the use of biopolymer materials in education